Ischiofemoral impingement resulting from a chronic avulsion injury of the hamstrings. (25th June 2014) - Hayat, Zara; Konan, Sujith; Pollock, Rob
Abstract : Significantly reduced distance between the ischium and the femur can result in symptomatic hip pain as a result of impingement. We present the case of a 16-year-old boy who presented with groin pain which had been affecting him for a year and a half following an innocuous football injury. Plain radiograph revealed a chronic apophyseal avulsion fracture of the ischium with excessive callus formation. CT scan and MRI revealed that the bony protuberance was responsible for symptomatic ischiofemoral impingement. In this case, he was successfully treated with non-operative management involving slow re-introduction to exercise. An unusual example of acquired ischiofemoral impingement, unrelated to surgery or significant trauma, this case highlights the need to consider such a diagnosis in otherwise unexplained groin pain.